2010
DOI: 10.2202/1542-6580.2115
|View full text |Cite
|
Sign up to set email alerts
|

Solid Pyrolysis Modelling by a Lagrangian and Dimensionless Approach--Application to Cellulose Fast Pyrolysis

Abstract: Many kinds of solids (e.g., biomass, thermoplastic and coal) thermally decompose according to similar types of kinetic pathways. They usually include a first step giving rise to more or less stable solid or liquid species followed by competitive reactions with formation of the final products (solids, vapours, and/or gases). In order to be extended to several types of solids, the present pyrolysis model relies on an original dimensionless Lagrangian approach. Mathematical equations of mass and heat balances are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 0 publications
2
12
0
Order By: Relevance
“…In addition, Lédé et al [31] have shown that cellulose kinetic constants can be used for representing the behavior of wood FP. Other published models (see, e.g., [9,12,32,33,60]) report similar qualitative results for the variations of T and T′. Moreover, nondimensional models show that our conclusions are valid for any type of solid undergoing a thermal decomposition.…”
Section: Conclusion and Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In addition, Lédé et al [31] have shown that cellulose kinetic constants can be used for representing the behavior of wood FP. Other published models (see, e.g., [9,12,32,33,60]) report similar qualitative results for the variations of T and T′. Moreover, nondimensional models show that our conclusions are valid for any type of solid undergoing a thermal decomposition.…”
Section: Conclusion and Discussionsupporting
confidence: 85%
“…They can likely been extended to any other types of processes implying solids thermal decompositions reactions [60].…”
Section: Other Considerationsmentioning
confidence: 99%
“…[2] shows also that any reaction of type (2) gives similar trends, inside extraordinary large domains of operating parameters, natures of solids, as well as values of enthalpies and chemical kinetics constants. These observations are also the same in the case of any solid undergoing more sophisticated kinetics (taking into account secondary reactions) as shown in a non dimensional modeling approach [26].…”
Section: Other Chemical Systemssupporting
confidence: 61%
“…In most of practical situations, the reactions with thick particles are carried out in conditions of fixed reactor temperature T H . Such cases have been the subject of numerous works (modelling and experiments) [12,15,16,24,25,26].…”
Section: Few Summarized Results In the Case Of Thick Particles (Biot mentioning
confidence: 99%
See 1 more Smart Citation